2021
DOI: 10.3390/diagnostics11040592
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Glioma Infiltration by the Combination of Multimodality Imaging and Artificial Intelligence, a Systematic Review of the Literature

Abstract: The aim of this study was to systematically review the literature concerning the integration of multimodality imaging with artificial intelligence methods for visualization of tumor cell infiltration in glioma patients. The review was performed in accordance with the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines. The literature search was conducted in PubMed, Embase, The Cochrane Library and Web of Science and yielded 1304 results. 14 studies were included in the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Closing this topic, we highlight a 2021 systematic review on the integration of multimodality imaging and artificial intelligence to improve the visualization of tumor cell infiltration in glioma [54], which found only two articles that included DLGG (along with HGG) in their cohorts [47,53], depicting the gap between low-grade and high-grade research.…”
Section: Flair Mri Cannot Reflect the Ptz: How Can Dlgg Delineation B...mentioning
confidence: 99%
“…Closing this topic, we highlight a 2021 systematic review on the integration of multimodality imaging and artificial intelligence to improve the visualization of tumor cell infiltration in glioma [54], which found only two articles that included DLGG (along with HGG) in their cohorts [47,53], depicting the gap between low-grade and high-grade research.…”
Section: Flair Mri Cannot Reflect the Ptz: How Can Dlgg Delineation B...mentioning
confidence: 99%
“…A recent systematic review concluded that the integration of machine learning with multiparametric data was promising for visualization of diffusely infiltrating tumor cells before and after treatment. The review also concluded that because study cohorts are small, further studies are required to determine optimal methodology, and there is a need for larger cohorts to improve model performance ( 90 ). An advantage of machine learning is that wide data can be handled relatively easily ( 91 ) which might allow the wide spectrum of advanced imaging signatures to be captured together and thereby improve performance accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperspectral imaging (HSI) has also been applied in conjunction with deep learning to identify the boundaries of glioblastomas 21 , but entails a much lower resolution (128.7 m pixel size vs. 0.2 m for THG). The same principle applies to MR imaging 18 , aside from the impractical setup, high costs and time-intensive workflow. Hollon et al 22 combined stimulated Raman histology (SRH) with deep learning to demonstrate the potential of label-free microscopy in conjunction with AI.…”
Section: Introductionmentioning
confidence: 95%
“…Computer-assistance of the neurosurgeon during a surgical procedure should result in instant, meaningful histological feedback of the tissue state. Artificial intelligence (AI) is capable of delivering state-of-the-art computer assisted diagnosis 16 18 . Deep learning, a subfield of AI, allows for complex pattern recognition by means of an iterative, supervised optimization process.…”
Section: Introductionmentioning
confidence: 99%